2005
DOI: 10.1002/adma.200401362
|View full text |Cite
|
Sign up to set email alerts
|

Biorelevant Calcification and Non‐Cytotoxic Behavior in Silicon Nanowires

Abstract: ExperimentalGlassy solid electrolytes in the Li 2 S±P 2 S 5 system were prepared by the mechanical milling technique [13]. Highly pure Li 2 S (Idemitsu Kosan Co., > 99.9 %) and reagent-grade P 2 S 5 (Aldrich, 99 %) crystalline powders were used as starting materials to prepare the 70Li 2 S´30P 2 S 5 (70 mol-% Li 2 S, 30 mol-% P 2 S 5 ) samples. The mixture of these materials was mechanically milled at room temperature by a planetary ball-mill apparatus (Fritsch Pulverisette 7) using an alumina pot (volume of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 25 publications
0
60
0
Order By: Relevance
“…Nagesha and coworkers have reported that SiNWs were non-cytotoxic to human kidney fi broblasts [ 28 ] and vertically aligned SiNW arrays provide a biocompatible interface for mammalian cell culture. [29][30][31] Given that AgNPs can readily decorate SiNWs, we reason that this process could provide a green approach to develop antibacterial materials with desirable biocompatibility.…”
Section: Doi: 101002/adma201001934mentioning
confidence: 98%
“…Nagesha and coworkers have reported that SiNWs were non-cytotoxic to human kidney fi broblasts [ 28 ] and vertically aligned SiNW arrays provide a biocompatible interface for mammalian cell culture. [29][30][31] Given that AgNPs can readily decorate SiNWs, we reason that this process could provide a green approach to develop antibacterial materials with desirable biocompatibility.…”
Section: Doi: 101002/adma201001934mentioning
confidence: 98%
“…The osteoconductivity of a material is widely assessed in vitro by measuring the rate of apatite formation in a SBF solution. [33][34][35] We found that lath-like bone HAp crystals formed in both hybrid fi lms ( Figure 3 A-b,B-b) after 4 d of incubation, in contrast to bare GO and graphene that does not undergo any further phase transition in aqueous solution. [ 10 ] The overall structure of CaCO 3 vaterite microspheres, which were wrapped by a GO or graphene network, was well preserved after the reduction process ( Figure S5, Supporting Information).…”
Section: Doi: 101002/adma201100010mentioning
confidence: 99%
“…[4][5][6] Apart from the application of SiNW-based transistors for the selective detection of biomolecules, relatively little has been reported on the biocompatibility of SiNWs that is necessary for evaluating potential applications of SiNWs as a biomaterial. SiNWs can be considered as a biomaterial because it possesses advantages over other inorganic materials such as polycrystalline metals [7] and significantly, the degradation products of Si nanomaterials are metabolically tolerant in vivo and are found mainly in the form of Si(OH) 4 . [7,8] Nagesha et al [7] have shown SiNW surface under influence of an electrical bias exhibits an interfacial behavior that promotes calcification in stimulated plasma and have demonstrated non-cytotoxic behavior using human kidney fibroblast cells.…”
mentioning
confidence: 99%
“…SiNWs can be considered as a biomaterial because it possesses advantages over other inorganic materials such as polycrystalline metals [7] and significantly, the degradation products of Si nanomaterials are metabolically tolerant in vivo and are found mainly in the form of Si(OH) 4 . [7,8] Nagesha et al [7] have shown SiNW surface under influence of an electrical bias exhibits an interfacial behavior that promotes calcification in stimulated plasma and have demonstrated non-cytotoxic behavior using human kidney fibroblast cells. Popat et al [9] have investigated improved osteoblast performance by using controlled SiNW structures.…”
mentioning
confidence: 99%